Theodor Pallady, 150 years since birth (Confluenţe Bibliologice, 2022)
In the article, the essential data related to the life and activity of the Romanian painter, the post-mortem member of the Romanian Academy Theodor Pallady (1871-1956) are reviewed. Pallady’s thematic collection is diverse, with nudes, landscapes, flowers and many self-portraits. The predilection of Theodor Pallady for still life is reflected and the desire to portray in a painting a fragment of the universal reality in all his poetry and harmony. It describes the circulation of postage stamp issues dedicated to the visual arts and to one of the masters of modern Romanian painting, whom he called “Theodor Pallady, 150 years”